TAXONOMIC AND ECOLOGICAL STRUCTURE OF THE EDAPHIC ALGAE FLORA FROM CERTAIN AGROCENOSES OF THE REPUBLIC OF MOLDOVA - Trofim, Alina; Donţu, Natalia; Gheorhiţa, Cristina; Şalaru, Victor (CEP USM, 2013)
The most part of territory of the Republic Moldova is covered by agro-ecosystems in which the algae play a fundamental role as they are considered indicators of soil quality. Soil samples were taken from different regions of the country on which are cultivated wheat, rape, potatoes and chick-pea and were analyzed within the Scientific Research Laboratory „Algaeology”, of the State University of Moldova during 2007 – 2010. All in all, in the taken samples there were found 100 species and intraspecific varieties: Cyanophyta – 82 species, Bacillariophyta – 8, Xanthophyta – 3, Euglenophyta – 2, Chlorophyta – 5. The richest diversity was found in the soils cultivated with wheat - 42 species and intra-specific varieties.

În Republica Moldova cea mai mare parte din teritoriu este ocupată de agroecosisteme, în care algele joacă un rol primordial în calitate de indicatoriaicalităţii solului. Studiul algelor ca parte componentă a oricărui tip de sol şi vegetaţie are o însemnătate atât teoretică, cât şi practică. Releveele de sol au fost colectate pe parcursul anilor 2007–2010din diferite regiuni ale ţării pe care se cultivă grâu, rapiţă, cartof şi năut şi analizate în laboratorul „Algologie” al USM. În total, în aceste probe au fost evidenţiate 100 de specii şi varietăţi intraspecifice: Cyanophyta–82 specii, Bacillariophyta–8, Xanthophyta–3, Euglenophyta–2, Chlorophyta–5specii . Cea mai mare diversitate a fost depistată în solurile ocupate de cultura de grâu –42 de specii şi varietăţi intraspecifice.
STRUCTURA TAXONOMICĂ ŞI ECOLOGICĂ A ALGOFLOREI EDAFICE DIN UNELE AGROCENOZE DIN REPUBLICA MOLDOVA
Keywords: algae flora; agro-ecosystem; cereal crops; ecological groups; eco-bimorphs; algofloră; agroecosisteme; culturi agricole; grupe ecologice; ecobiomorfe